2016
DOI: 10.1117/12.2228458
|View full text |Cite
|
Sign up to set email alerts
|

Large area patterning using interference and nanoimprint lithography

Abstract: Interference lithography (IL) is the best suited technology for the origination of large area master structures with high resolution. In prior works, we seamlessly pattern areas of up to 1.2 x 1.2 m2 with periodic features, i.e. a diffraction grating with a period in the micron range. For this process we use an argon ion laser emitting at 363.8 nm. Thus, feasible periods are in the range of 100 μm to 200 nm. Edge-defined techniques or also called (self-aligned) double patterning processes can be used to double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The patterning coverage area can also be expanded by longer expansion of the beams with a higher laser power. Recently, Bläsi et al [ 87 ] demonstrated the fabrication of nanostructures of 200 nm in periodicity uniformly over a surface area of 1.2 m × 1.2 m. After the creation of the nanopatterns, a mixture solution of hydrogen peroxide and ammonia were used to release the membrane from the silicon substrate via bubbling [ 88 ]. This results in the floatation of the membrane on the solution-free surface ( Figure 9 a).…”
Section: Compliant Stencil Maskmentioning
confidence: 99%
“…The patterning coverage area can also be expanded by longer expansion of the beams with a higher laser power. Recently, Bläsi et al [ 87 ] demonstrated the fabrication of nanostructures of 200 nm in periodicity uniformly over a surface area of 1.2 m × 1.2 m. After the creation of the nanopatterns, a mixture solution of hydrogen peroxide and ammonia were used to release the membrane from the silicon substrate via bubbling [ 88 ]. This results in the floatation of the membrane on the solution-free surface ( Figure 9 a).…”
Section: Compliant Stencil Maskmentioning
confidence: 99%
“…Moreover, it has become a perfect match for some emerging application fields that are in great need of largearea patterning of submicro and nanoscale features at a low cost, such as patterned magnetic media, high-brightness light-emitting diodes (HB-LEDs), anti-reflective coatings or films, flexible electronics, printed electronics, OLED, wire grid polarizer, flat panel display, microfluidic devices, etc. In particular, this technique has demonstrated great commercial prospects in several market segments, HB-LEDs, anti-reflective coatings or films with moth-eye structures, flexible electronics, solar cells, architectural glass, WGP, optical elements, patterned media, micro-lens arrays, and functional polymer devices [1][2][3][4][5][38][39][40][41]. Large-Area Nanoimprint Lithography and Applications http://dx.doi.org/10.5772/intechopen.72860…”
Section: Applications Of Large-area Nilmentioning
confidence: 99%
“…Large-area nanopatterning has demonstrated great potential which can significantly enhance the performance of many devices and create innovative products, such as LEDs, solar cells, hard disk drives, laser diodes, displays, sub-wavelength optical elements, antireflective glass with moth's eye structures, flexible electronics, OLED, etc. [1][2][3][4][5][6][7]. For example, the solar cells with submicro anti-reflective coating exhibited higher photocurrent and higher power conversion efficiency compared to those without nanostructures [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ideal moldable materials gathering all the required properties can be found in organic polymers. They can be processed with high throughput soft-nano imprint lithography (NIL) methods 19,20,21 ,…”
Section: Introductionmentioning
confidence: 99%